Nine new species of Enithares (Heteroptera: Notonectidae) from New Guinea, with distributional notes on other species and an updated world checklist - Polhemus, Dan A. (Zootaxa, 2020)
Nine new species of Enithares are described from New Guinea and immediately adjacent islands: E. peninsularis from the Owen Stanley Mountains of the Papuan Peninsula, E. bosavi and E. papua from southern Papua New Guinea, E. orsaki from northern Papua New Guinea, E. insularis from the D’Entrecasteaux Islands, E. tagula from the Louisiade Archipelago, E. ziwa from the central mountains of western New Guinea, E. arfak from the Arfak Mountains of the eastern Vogelkop Peninsula, and E. kasim from the western Vogelkop Peninsula. Enithares bakeri is newly recorded from New Guinea, and in combination with the new species described above brings the total number of species of Enithares in New Guinea to 16, and the regional total to 19 when including nearby islands of Waigeo, Biak, the D’Entrecasteaux group, and the Louisiade Archipelago. The species concept of E. atra is clarified and geographically restricted to southeastern New Guinea; specimens previously recorded under this name from northern New Guinea are shown to represent the new species E. orsaki. Additional distribution records for 15 previously described Enithares species are provided for many localities in the Malay Archipelago and mainland Southeast Asia, including the first records of E. bakeri from Lombok, Flores, Timor, Halmahera, and Obi; the first record of E. paramegalops from Ambon; the first records of E. gibbera from Kolombangara and Malaita in the Solomon Islands; the first record of E. intricata from Bali; the first records of E. lombokensis from Flores and Sumba; the first records of E. ripleyana from Halmahera, Ternate and Tidore; and the first record of E. ciliata from Borneo. Photomicrographs of key characters and distribution maps are provided for all new species described, accompanied by an updated world checklist for the genus with distributional notes and associated references.